Model Return on Equity in relation to Oil Price and Loan to Deposit Ratio - Soehaditama, Josua Panatap; Manurung, Adler Haymans; Machdar, Nera Marinda; Munir, Ningky Sasanti (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research can present an in-depth understanding of how companies and financial institutions deal with market complexity, improve financial performance, and innovate in the face of challenges and opportunities that arise in the current economic context. Using quantitative research methods with statistical regression models as analysis so that it can be used to evaluate the quantitative relationship between LDR, oil prices, and ROE, with the number of respondents of all bank issuers listed on the Indonesia Stock Exchange and submitting complete financial statements. There is a positive and significant influence between the Bank's LDR variable and ROE, both a significant and positive influence between the Oil Price variable and ROE, simultaneously also have a positive and significant effect. This result, although positive, does not mean that there needs to be improvement in management in an effort to improve results for the company.